PARADIGMA PEMBELAJARAN DALAM PERSPEKTIF TARBIYAH ULUL ALBAB DAN MULTIPLE INTELLIGENCES - Abdul Halim Fathani (lp2m-uin malang, 2014)
Oleh: Abdul Halim Fathani Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Malang Email: ah.fathani@gmail.com Abstract Education is the nature of the development process so learners are able to form an ideal of human personality (ulul albab). The theory of multiple-intelligences have assured to every educator that each learners is a bright child, owned by type of intelligence as innate or developed because of the culture. Learning paradigm designed tarbiyah ulul-albab, must be able to internalize aspects of dhikr, fikr, and amal shaleh that develop four forces: spiritual depth, morality, breadth of knowledge, and professional maturity.